The Economic Theory of Regulation and Public Financing of Presidential Elections - Abrams, Burton A.; Settle, Russell F. (Journal of Political Economy, 1978)
Recent changes in campaign finance legislation (passed by a heavily Democratic Congress) are considered within the context of the two competing theories of regulation, the "public-interest" theory and the economic theory of regulation. Empirical evidence is presented in support of the economic theory's explanation for these major regulatory changes in the political process. The evidence suggests that these changes were highly beneficial to the Democratic party and that they were instrumental in Jimmy Carter's defeat of Gerald Ford in the 1976 presidential election.